THE IMPORTANCE OF SOCIO-PEDAGOGICAL EDUCATION IN THE DEVELOPMENT OF THE SPIRITUAL, LEGAL CULTURE OF GIRLS IN THE FAMILY - Tojiboyeva Sevara Hayrullayevna (Galaxy International Interdisciplinary Research Journal, 2023)
In family upbringing, the behavior of the mother is transferred to the daughter. According to this, our wise people say, "See the mother and take the daughter." In the upbringing of a girl child, the main signs that make up her moral qualities are: modesty, chastity, manners, intelligence, modesty, eloquence, modesty and sophistication.